Effects of swimming training on the femoral neck strength in growing rats with untreated streptozotocin-induced diabetes - da Silva, Ana Karina; Del Carlo, Ricardo Junqueira; da Matta, Sérgio Luis Pinto; Louzada, Mario Jefferson Quirino; Rodrigues, Aurora Corrêa; da Silva, Márcia Ferreira; Drummond, Lucas Rios; de Castro, Cynthia Aparecida; Silva, Carlos Henrique Osorio; Natali, Antônio José (My University, 2014)
Background: While type 1 diabetes mellitus (T1DM) increases bone fragility physical exercise improves bone quality and strength. Research question: To test whether swimming training attenuates the deterioration of femoral neck structural and mechanical properties in growing rats with untreated streptozotocin (STZ)-induced T1DM. Type of study: Randomised controlled study. Methods: Male Wistar rats (4-weeks-old; initial body weight: 80-90 g) were divided into 4 groups of 10 animals: diabetes sedentary (DS; 60 mg/kg of STZ, single i.p.); diabetes exercised (DE; 60 mg/kg of STZ, single i.p.); control sedentary (CS, same single dose of vehicle); and control exercised (CE, same single dose of vehicle). Six weeks later animals from DE and CE groups underwent a low- intensity swimming training (5 sessions/wk, 90 min/session, load: 4% of body weight) for 8 weeks. The femoral neck mechanical properties were measured. Bone mineral density (BMD) and mineral content (BMC), as well as the femoral neck bone volume (BV/TV) and collagen content were assessed. Results: Rats with T1DM exhibited reduced body weight, femoral weight and length, BMC and BMD, femoral neck collagen content, BV/TV, trabecular thickness, maximum load, stiffness and tenacity, and increased trabecular spacing compared to controls. Swimming training increased femoral BMC and BMD, femoral neck collagen content, BV/TV, trabecular thickness, stiffness and yield point energy, and reduced trabecular spacing in control animals, but not in T1DM animals. Conclusion: Low-intensity swimming training seems to be ineffective in attenuating the deterioration of the femoral neck structural and mechanical properties in growing rats with untreated STZ-induced T1DM.
Keywords: Bone resistance; Exercise; Hip fracture; Osteopenia; Physical activity